War is beautiful an American ambulance driver in the Spanish Civil War - Neugass, James 1905-1949 (New Press Distributed by W.W. Norton & Co., 2008)
A memoir based on the recently discovered journals of an award-winning poet on the front lines as a member of the Abraham Lincoln brigade in Spain recounts his efforts to counter European fascism, service as an ambulance driver, and efforts to rescue wounded soldiers from the battlefield. 20,000 first printing